How does one solve ${\log _2}x = {\log _4}(x + 6)$ ?
Answer
Verified
442.2k+ views
Hint:For simplifying the original equation , firstly used logarithm property
${\log _b}a = \dfrac{{{{\log }_x}a}}{{{{\log }_x}b}}$ then take base two exponential of both sides of the equation, then apply the logarithm formula ${b^{{{\log }_b}a}} = a$ to simplify the given equation .
Formula used:
We used logarithm properties i.e.,
${\log _b}a = \dfrac{{{{\log }_x}a}}{{{{\log }_x}b}}$
And
${b^{{{\log }_b}a}} = a$ , the logarithm function says $\log x$ is only defined when $x$ is greater than zero.
Complete solution step by step:
It is given that ,
${\log _2}x = {\log _4}(x + 6)$ ,
We have to solve for $x$ .
Now using logarithm property ${\log _b}a = \dfrac{{{{\log }_x}a}}{{{{\log }_x}b}}$ ,
We will get,
${\log _2}x = \dfrac{{{{\log }_2}(x + 6)}}{{{{\log }_2}(4)}}$
Now , simplify the equation , we will get the following result ,
$ \Rightarrow {\log _2}x = \dfrac{{{{\log }_2}(x + 6)}}{{{{\log }_2}{{(2)}^2}}}$ (using $\log {a^b}
= b\log a$)
$ \Rightarrow {\log _2}x = \dfrac{{{{\log }_2}(x + 6)}}{{2{{\log }_2}(2)}}$
Using ${\log _a}a = 1$ ,
$ \Rightarrow {\log _2}x = \dfrac{{{{\log }_2}(x + 6)}}{2}$
$
\Rightarrow 2{\log _2}x = {\log _2}(x + 6) \\
\Rightarrow {\log _2}{(x)^2} = {\log _2}(x + 6) \\
$ (using $\log {a^b} = b\log a$)
Now , by assuming the base of the logarithm to be $2$ ,then take the base $2$ exponential of both sides of the equation, we will get the following result ,
For equation one ,
${2^{{{\log }_2}\left( {{x^2}} \right)}} = {2^{{{\log }_2}(x + 6)}}$
By applying the logarithm formula ${b^{{{\log }_b}a}} = a$ . we will get the following result ,
${x^2} = x + 6$
Or
${x^2} - x - 6 = 0$
$
\Rightarrow {x^2} - 3x + 2x - 6 = 0 \\
\Rightarrow x(x - 3) + 2(x - 3) = 0 \\
\Rightarrow (x + 2)(x - 3) = 0 \\
\Rightarrow x = - 2 \\
and \\
x = 3 \\
$
Now recall that the logarithm function says $\log x$ is only defined when $x$is greater than zero.
Therefore, in our original equation ${\log _2}x = {\log _4}(x + 6)$ ,
Here,
$
(x) > 0 \\
and \\
(x + 6) > 0 \\
$ ,
When $x = - 2$ , it is less than zero.
Therefore , we reject $x = - 2$ .
And when $x = 3$ , it is greater than zero .
Therefore, we have our solutions i.e., $x = 3$ .
Note: The logarithm function says $\log x$ is only defined when $x$ is greater than zero. While defining logarithm function one should remember that the base of the log must be a positive real number and not equals to one . At the end we must recall that the logarithm function says $\log x$ is only defined when $x$ is greater than zero. While performing logarithm properties we have to remember certain conditions , our end result must satisfy the domain of that logarithm .
${\log _b}a = \dfrac{{{{\log }_x}a}}{{{{\log }_x}b}}$ then take base two exponential of both sides of the equation, then apply the logarithm formula ${b^{{{\log }_b}a}} = a$ to simplify the given equation .
Formula used:
We used logarithm properties i.e.,
${\log _b}a = \dfrac{{{{\log }_x}a}}{{{{\log }_x}b}}$
And
${b^{{{\log }_b}a}} = a$ , the logarithm function says $\log x$ is only defined when $x$ is greater than zero.
Complete solution step by step:
It is given that ,
${\log _2}x = {\log _4}(x + 6)$ ,
We have to solve for $x$ .
Now using logarithm property ${\log _b}a = \dfrac{{{{\log }_x}a}}{{{{\log }_x}b}}$ ,
We will get,
${\log _2}x = \dfrac{{{{\log }_2}(x + 6)}}{{{{\log }_2}(4)}}$
Now , simplify the equation , we will get the following result ,
$ \Rightarrow {\log _2}x = \dfrac{{{{\log }_2}(x + 6)}}{{{{\log }_2}{{(2)}^2}}}$ (using $\log {a^b}
= b\log a$)
$ \Rightarrow {\log _2}x = \dfrac{{{{\log }_2}(x + 6)}}{{2{{\log }_2}(2)}}$
Using ${\log _a}a = 1$ ,
$ \Rightarrow {\log _2}x = \dfrac{{{{\log }_2}(x + 6)}}{2}$
$
\Rightarrow 2{\log _2}x = {\log _2}(x + 6) \\
\Rightarrow {\log _2}{(x)^2} = {\log _2}(x + 6) \\
$ (using $\log {a^b} = b\log a$)
Now , by assuming the base of the logarithm to be $2$ ,then take the base $2$ exponential of both sides of the equation, we will get the following result ,
For equation one ,
${2^{{{\log }_2}\left( {{x^2}} \right)}} = {2^{{{\log }_2}(x + 6)}}$
By applying the logarithm formula ${b^{{{\log }_b}a}} = a$ . we will get the following result ,
${x^2} = x + 6$
Or
${x^2} - x - 6 = 0$
$
\Rightarrow {x^2} - 3x + 2x - 6 = 0 \\
\Rightarrow x(x - 3) + 2(x - 3) = 0 \\
\Rightarrow (x + 2)(x - 3) = 0 \\
\Rightarrow x = - 2 \\
and \\
x = 3 \\
$
Now recall that the logarithm function says $\log x$ is only defined when $x$is greater than zero.
Therefore, in our original equation ${\log _2}x = {\log _4}(x + 6)$ ,
Here,
$
(x) > 0 \\
and \\
(x + 6) > 0 \\
$ ,
When $x = - 2$ , it is less than zero.
Therefore , we reject $x = - 2$ .
And when $x = 3$ , it is greater than zero .
Therefore, we have our solutions i.e., $x = 3$ .
Note: The logarithm function says $\log x$ is only defined when $x$ is greater than zero. While defining logarithm function one should remember that the base of the log must be a positive real number and not equals to one . At the end we must recall that the logarithm function says $\log x$ is only defined when $x$ is greater than zero. While performing logarithm properties we have to remember certain conditions , our end result must satisfy the domain of that logarithm .
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE